2020
DOI: 10.1186/s13148-019-0800-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HDAC activity and altered histone phospho-acetylation confer acquired radio-resistant phenotype to breast cancer cells

Abstract: Background: Poor-responsiveness of tumors to radiotherapy is a major clinical problem. Owing to the dynamic nature of the epigenome, the identification and targeting of potential epigenetic modifiers may be helpful to curb radio-resistance. This requires a detailed exploration of the epigenetic changes that occur during the acquirement of radio-resistance. Such an understanding can be applied for effective utilization of treatment adjuncts to enhance the efficacy of radiotherapy and reduce the incidence of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Most remarkably, radiated mitotic cells adopted a more de-condensed chromatin con guration after cell cycle progression, which correlated with their reduced cell survival. This observation is in complete concordance with our recent report that suggests increased heterochromatinization upon acquirement of radio-resistance (44). Hence, these data strongly indicate that global chromatin con guration plays an essential role in determining cell fate towards radiation induced DNA damage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Most remarkably, radiated mitotic cells adopted a more de-condensed chromatin con guration after cell cycle progression, which correlated with their reduced cell survival. This observation is in complete concordance with our recent report that suggests increased heterochromatinization upon acquirement of radio-resistance (44). Hence, these data strongly indicate that global chromatin con guration plays an essential role in determining cell fate towards radiation induced DNA damage.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, histone PTM alterations that occur in response to DNA damage could be a cell cycle phase speci c event (39)(40)(41). Earlier studies from our group reported a dynamic kinetics of H3S10ph, observed only during the DDR of the relatively radioresistant G 0 /G 1 phase (42,43) Our recent report also indicates an association of altered histone phosphoacetylation with breast cancer radio-resistance (44). These reports suggest that a distinct interplay of H3 phospho-acetylation could regulate cell cycle phase speci c radio resistance.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…After exposure to high doses of sparsely ionizing radiation or even low doses of densely ionizing radiation, there is a serious risk that numerous and possibly clustered DSBs will not be repaired in a timely manner, leading to separation of broken DNA ends, misrejoining of these ends, and formation of often lethal chromosomal aberrations. These events probably explain why fast repair mechanisms have evolved and are preferred by organisms with large genomes [5]. However, a fast rate of repair may be at the expense of repair accuracy, resulting in smaller mutations, some of which may be carcinogenic and thus no less dangerous than larger mutations.…”
Section: Global Versus Local Dsb Repair Pathway Selection and Regulationmentioning
confidence: 99%
“…Preclinical study in lung carcinoma cells showed that HDAC inhibitor SAHA could sensitize these cells to radiation with minimum effects to normal cells that would enhance the effect of radiotherapy of the cancer cells [194]. Another preclinical study in breast cancer cells MCF7, proved that a proper balance between HDACs and HATs is necessary to maintain the histone acetylation thereby the compaction of the chromatin to resist the development of resistant of cancer cells to radiation therapy [195]. So, an early diagnosis of tumor HDAC activity would increase the efficiency of HDAC/radiotherapy strategy of treating cancer cell [196].…”
Section: Clinical Trialsmentioning
confidence: 99%